Cross-Regional Capacity Mechanism for Emergency Power Support in Extreme Weather Events - WU Zifeng, YUAN Jiahai, ZHANG Jian, ZHANG Haonan (Dianli jianshe)
The increasing frequency of extreme weather events pose significant challenges to power system security. The expedited development of cross-regional capacity mechanisms has emerged as an effective strategy to improve the emergency response capabilities of power systems and ensure a reliable power supply. First，the effects of extreme weather on power systems are discussed，followed by a review of pilot implementations of capacity mechanisms across various locations in China. Based on cross-regional supply and demand theory，the architectural design of the cross-regional capacity mechanism is enhanced by incorporating three critical components： mechanism boundaries and regulations，lower and upper bounds of the capacity compensation price，and frameworks for responsibility and penalties. Subsequently，a novel cross-regional emergency power support capacity price model is developed，integrating the cost of the new entry （CONE） model，net income per unit of installed capacity，and the Value of Lost Load indicator. Furthermore，a scenario-based analysis is applied to determine the lower and upper bounds of the capacity compensation price for coal-fired power units participating in cross-regional emergency power support within the electricity market during extreme weather conditions. The results indicate that the lower bound of the capacity compensation price represents 30%-70% of the fixed costs of a coal power unit，aligning with the short- to medium-term tariff structure outlined by China’s present coal power capacity mechanism （30%-50%）. The upper bound of the capacity compensation price must be adjusted upward to signal a capacity shortage，as reflected in the increasing loss of load expectation （LOLE）. Finally，targeted recommendations for optimizing capacity mechanisms are presented.